Evaluation of surgical treatment outcomes in patients with laryngeal cancer during a 5-year follow-up - Morshed, Kamal; Lewicki, Marcin; Bojarczuk, Katarzyna; Tarasiuk-Staniak, Agnieszka; Smoleń, Agata (Family Medicine & Primary Care Review, 2016)
Background. Recurrences are the main cause of failure in the treatment of laryngeal cancer. The outcome depends both on the success of treatment of the primary tumour and the procedure used to treat the recurrence. Objectives. Evaluation of the incidence of recurrences in patients treated surgically for laryngeal cancer during a 5-year follow-up. Material and methods . The study group consisted of 123 patients treated for laryngeal squamous cell carcinoma. Surgical treatment was used in all patients. Total laryngectomy was conducted in 85 (69.1%) patients, while endoscopic laser resection of the tumour was conducted in 38 (30.9%) patients. Results . Local recurrence occurred in 15 (12.2%) patients, lymph node recurrence occurred in 10 (8.1%) patients, and local and lymph node recurrence occurred in 8 (6.5%) patients. In total, recurrences occurred in 33 (26.8%) patients, and distant metastases occurred in 15 (12.2%) patients. The incidence of recurrences during the 5-year follow-up increased significantly with the increase of the T feature (p = 0.02), N feature (p = 0.01), stage of clinical progression (p = 0.003), and histological malignancy G stage (p = 0.002). The incidence of recurrences also depended on the origin of the cancer. In the glottic area, recurrences were significantly less frequent than in the epiglottic area (p = 0.009). Multiple factor analysis revealed that the presence of recurrences (p < 0.00001) was an important independent prognostic factor in the investigated group of patients with laryngeal cancer during the follow-up. Conclusions . Recurrences most often occur in patients with an epiglottic tumour at stages T3 and T4 of local progression, patients with metastases to lymph nodes, patients at stages III and IV of clinical progression, and patients with poorly differentiated squamous cell carcinoma (G3). Patients with local recurrences have a significantly worse prognosis than those without recurrences. The presence of recurrences is an important independent prognostic factor.